2020
DOI: 10.5539/jas.v12n8p245
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiles and Anti-termite Activity of Hydrodistillation Residues From Three Aromatic Plants Acclimated in Burkina Faso

Abstract: Distillation process of aromatic plants produces a considerable amount of solid residues, which are rich in secondary metabolites known as bioactive compounds. In this context, residues from hydrodistillation of selected aromatic plants such as Mentha piperita L., Cymbopogon citratus Stapf and Eucalyptus camaldulensis Dehnh, have been studied for their total polyphenol content using Folin-Ciocalteu Reagent (FCR) method, total flavonoid content using aluminium chlorid (AlCl3) and antioxidant properties were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…A concentration of only 10% is therefore an effective concentration for ethanolic extracts of Eucalyptus camaldulensis. Similar results were obtained by (Sankara et al, 2020) and (Bonzi-Coulibaly et al, 1997), according to whom ethanolic extracts obtained from solid residues after hydrodistillation are generally richer in total phenolic compounds and flavonoids with antifungal activity. In all cases, mycelial growth decreased as the concentration of extract in the medium increased.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A concentration of only 10% is therefore an effective concentration for ethanolic extracts of Eucalyptus camaldulensis. Similar results were obtained by (Sankara et al, 2020) and (Bonzi-Coulibaly et al, 1997), according to whom ethanolic extracts obtained from solid residues after hydrodistillation are generally richer in total phenolic compounds and flavonoids with antifungal activity. In all cases, mycelial growth decreased as the concentration of extract in the medium increased.…”
Section: Discussionsupporting
confidence: 85%
“…Ethanol (70%) is known to be more effective for extracting polyphenols than water. (Sankara et al, 2020) evaluated the polyphenol content and antioxidant activity of ethanolic extracts obtained from solid residues after hydro-distillation. Generally speaking, these extracts are richer in total phenolic compounds and flavonoids, which justify the antitremite and antifungal activities.…”
Section: Discussionmentioning
confidence: 99%
“…This is together with the phenolic compounds that are extracted from the solid residue of the hydrodistillation of R. o cinalis, which have a deterrent effect on pest insects (Sánchez-Vioque et al, 2015). Sankara et al (2020) reported that the residues from the hydrodistillation of Eucalyptus camaldulensis could provide interesting bioactive compounds, as new anti-termite agents in plant protection. Mahmoudi et al (2020) also reported that hydrodistilled basil leaves (Ocimum basilicum) have a good repellent activity against the stored grain pests, Tribolium castaneum.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the solid residue of rosemary is rich with non-volatile bioactive compounds known as secondary metabolites, including phenolic acids and phenolic diterpenes such as rosmarinic acid, caffeic acid, carnosic acid, carnosol, as well as some flavonoids. These constituents are known to be potent antioxidants, antimicrobial, antiproliferative, anticancer, anti-diabetic, anti-inflammatory, anti-viral, and anti-atherogenic [11][12][13][14][15][16][17][18]. Each feature makes these residues useful as health-promoting compounds, as ingredients for anti-aging agents in cosmetics products, and as antioxidant food additives, simultaneously increasing the crop's profit.…”
Section: Introductionmentioning
confidence: 99%